Multifaced Approach in Reducing Stunting in Semarang Municipality: a Policy Brief - Agushybana , Farid; Ashari, Ayu; Nuridzin, Dion Zein; Hakam, Mochamad Abdul; Siramaneerat, Issara; Fitri, Ichlasia Ainul (Public Health of Indonesia, 2025)
Background: Stunting is a serious public health problem globally, and it is associated with increased morbidity and mortality rates, reduced cognitive development, and lower economic productivity in adulthood. Therefore, understanding the factors contributing to stunting incidence is crucial in developing effective interventions to address this issue.Objectives: This study analyzes factors influencing stunting in Semarang using SEM-PLS to support evidence-based interventions for improving nutrition, healthcare, and environmental conditions, aiming to reduce stunting and enhance community well-being.Methods: This study involved 556 Children aged 0-59 months old. This study drew samples randomly from across sub-districts in Semarang. The outcome variable was the stunting status, while the latent variables were child characteristics, family characteristics, maternal factors, parenting, accessibility to health service, dietary habits, nutrition and food habits, specific intervention, Posyandu involvement, infectious diseases, and environmental factors. This study employed the structural equation modeling-partial least square (SEM-PLS) to analyze the relationship between several latent variables.Results: The results suggest that child characteristics, environmental factors leading to infectious disease, maternal factors, infectious disease itself, nutritional intake, specific intervention, and socioeconomic factors have a direct positive effect on stunting incidence. To overcome the stunting problem in Semarang, we present seven policy options that target the root causes and implement prevention and reduction of stunting incidents.Conclusions: The main principles for overcoming stunting in Semarang are "enhance child nutrition programs", "strengthen infectious disease prevention", "improve maternal and child healthcare", "enhance socioeconomic support", "strengthen sensitivity intervention", "foster collaboration and coordination", and “conduct targeted awareness campaigns”. By implementing policy recommendations that focus on improving nutrition, enhancing healthcare services, addressing environmental factors, and promoting socioeconomic development, it is possible to reduce stunting incidence rates and improve the overall well-being of children. Keywords: stunting; malnutrition; undernutrition; Semarang; policy brief